A Research On The Potential Of Local Natural Fiber To Produce Handmade Papers For Drawing, Painting And Printmaking - Darestani, Elham Shafaei (2013)
Paper is made of a raw material that has been beaten and broken down into tiny fibres, mixed with water and formed into sheets on a screen surface that catches the fibres as the water drains through it. The individual fibres interlock and form a sheet of paper when pressed and dried. The raw materials producing such fibres include the bast plants, tree bark, stalks of grasses, and other vegetation. The modernization of papermaking made it possible for mass-production of paper using pulped woods. The invention of pulping machine would end the nearly 2000-year use of pulped rags and plant fibres, and start a new era for the production of newsprint. Eventually almost all paper that we know today is made out of pulped wood. However, industrialized papers made from wood pulp are not suitable to be used for artworks. This is because industrialized papers have high acid content due to the processing of the wood pulp. Acidic papers must be avoided at all cost by artists because these papers turn yellow quickly in time, negatively affecting the durability and aesthetic value of the art work. Therefore, rather than relying on the industrial process of papermaking the production of art papers that is used for drawing, printmaking and painting remains heavily based on the handmade process. This research investigated the potential of natural fibres available locally to produce specialized hand-made art papers for drawing and painting. It intended to further develop the existing research on hand-made papers at the USM School of Arts towards a specific application to produce hand-made papers specifically tailored for artistic use. Papers were made from natural fibres obtained from banana, kantan and mengkirai for artistic purposes. The handmade papers were then evaluated through performing laboratory tests and assessed by several well-known Malaysian artists to compare their performance against commercial papers.